Sustainable Masjid architecture and public buildings - Tohid, Zainon; Abdul Rahim, Asiah (Elsevier Ltd., 2015)
This paper explores the approaches related to sustainable Masjid architecture and public buildings. Example masjid is a place of great importance for Muslims for worship, to seek a feeling of peace and serenity. Nowadays Masjid becomes more complex and have higher expectation by Muslim community from all ages. The methodology used will be table research from literature review. Analysis will be through observation and secondary data. This paper will conclude that further research will be done to identify rules and guidelines to assist players in building industry and other stakeholders to include green and sustainable into planning, design, construction and maintenance of built environment.